2020
DOI: 10.1186/s13643-020-01292-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between community mental health nursing and hospital admissions for people with serious mental illness: a systematic review

Abstract: Background: Relapse prevention is an important objective in the management of serious mental illness (SMI). While community mental health nurses (CMHN) might be well-placed to support people with SMI in averting relapse, no systematic reviews have examined this association. Aim: To review the evidence from studies reporting an association between CMHN exposure and hospitalisation of persons living with SMI (a proxy for relapse). Methods: Searches were undertaken in ten bibliographic databases and two clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The phenomenon of deinstitutionalisation, instigated by the rise of the mental patients civil rights movement, the mobilisation of mental health advocacy organisations and, to some extent, the rise of neoliberal policies, has contributed to the development of new forms of community-based treatment for people with mental disorders (Nakhost et al, 2018). Several therapeutic approaches and models have emerged in recent decades to enable the care and monitoring of sick people in their own living environment (Leach et al, 2020;Molodynski et al, 2016). These include the assertive community treatment model (ACT; Weinstein et al, 2011) and forensic assertive community treatment (FACT) teams for forensic mental health follow-up (Lamberti et al, 2014;Marquant et al, 2016), which are an increasingly common mechanism in the community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of deinstitutionalisation, instigated by the rise of the mental patients civil rights movement, the mobilisation of mental health advocacy organisations and, to some extent, the rise of neoliberal policies, has contributed to the development of new forms of community-based treatment for people with mental disorders (Nakhost et al, 2018). Several therapeutic approaches and models have emerged in recent decades to enable the care and monitoring of sick people in their own living environment (Leach et al, 2020;Molodynski et al, 2016). These include the assertive community treatment model (ACT; Weinstein et al, 2011) and forensic assertive community treatment (FACT) teams for forensic mental health follow-up (Lamberti et al, 2014;Marquant et al, 2016), which are an increasingly common mechanism in the community.…”
Section: Introductionmentioning
confidence: 99%
“…The mental health nursing role within these different community teams is central and significant (Cuddeback & Shattell, 2010;Leach et al, 2020;Wallace et al, 2005;Waynor & Dolce, 2015), as it is in compulsory community care (O'Brien et al, 2009;Paradis-Gagné et al, 2021). However, nursing research on issues related to treatment under coercion has been limited, particularly at the theoretical and philosophical levels.…”
Section: Introductionmentioning
confidence: 99%
“…One previous systematic review examined the association between mental health-nursing skill mix and relapse [ 27 ]. The review, focused on community mental health nurses and included two studies, involving 356 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The review, focused on community mental health nurses and included two studies, involving 356 patients. The studies were rated as having a low–moderate risk of bias [ 27 ]. The authors reported that there was not enough evidence to conclude that community mental health nursing reduced the risk of admission to psychiatric inpatient facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation